'Get Your Indexing Shot in the Arm': American Society for Indexing (ASI) 2021 conference. (1st September 2021) - Kingdom, Ann
Abstract : Benefiting from lessons learnt during the hastily organized 2020 online conference, the American Society for Indexing's 2021 conference was a less intensive affair, with six presentations spread over two days and a little more time allowed for breaks. With over 70 participants from around the world, this was another international affair, with a wide-ranging programme covering the practice of indexing (working more efficiently, embedded indexing), career development, unusual indexing projects (the Mueller report index), and more thought-provoking topics (indexing through the ages, the challenges of musical literature). There was even time for some networking and informal discussion during the 'Happy Hour' at the end of the first day.